COMPARATIVE STUDY OF PLASMA MEMBRANE INTEGRITY OF I SPERMATOZOA BY USING HOS MEDIUM AND DISTILLED WATER AND THEIR RELATION WITH POST THAW MOTILITY - SHUKLA, M K; SAHA, SUJIT; RATHORE, K S; MISHRA, G K; SIDDQUI, M U; SAXENA, S K (The Indian Journal of Animal Reproduction, 2023)
This study was carried out on 148 frozen thawed semen, samples from cattle (58 from 11 HF bulls, 36 from7 crossbred bulls, 33 from 6 Sahiwal bulls and 21 from 4 Jersey bulls} and 57 frozen thawed semen samples from11 buffalo bulls maintained at Animal Breeding Centre (a Unit of ABRO India), Salon, Rae Bareli, UP. Plasmamembrane integrity of cryopreserved sperms was studied with the help of HOS solution (Osmolarity 0.080 Osmole/kg, pH 7.31) and double distilled water (Osmolarity 0.001 Osmole/kg, pH 5.93). The mean percentages of HOSreactive sperms in HOS solution and double distilled water for cattle and buffalo were 57.61±0.57, 48.98±0.34 and57 .06±0. 75, 47 .14±0.34, respectively. Except. Crossbred, the percentage of HOS reactive sperms in HOS solutionwas significantly (P
Keywords: HOS medium; Plasma membrane integrity; HOS reactive sperms; Cattle; Buffalo; Post Thaw motility